The Recent Challenges of Medical Education in Georgia and the Ways to Deal with - Our Approach - Tsilosani, Nino; Khimshiashvili, Nino; Tegetashvili, Ana (European Scientific Journal, ESJ, 2022)
It is generally believed that a global education crisis occurs within the health care occupations. There are several reasons that cause this condition, such as the discrepancy between educational systems and basic needs of the health care system, the rapidly-changing, complicated and dangerous environment (e.g., The COVID-19 pandemic) the problems with the disability of applying students’ theoretical knowledge in a harmless clinical environment, especially in the condition of mentor’s scarcity. At least – out of date system of medical education, where the emphasis is on getting knowledge and not its practical application. The article concerns our viewpoint and the ways, medical education can be improved upon in Georgia.